2010
DOI: 10.32607/20758251-2010-2-4-58-65
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of Xenobiotic Detoxication and Repair Genes with Malignant Brain Tumors in Children

Abstract: This study presents the results of research on DNA polymorphism in children with malignant brain tumors (172 patients, 183 in the control group). Genotyping was performed using an allele-specific tetraprimer reaction for the genes of the first (CYP1A1 (2 sites)) and second phases of xenobiotic detoxication (GSTM1, GSTT1, GSTP1, GSTM3), DNA repair genesXRCC1, XPD(2 sites),OGG1, as well asNOS1andMTHFR.The increased risk of disease is associated with a minor variant ofCYP1A1(606G) (p = 0.009; OR = 1.50) and a del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The expression levels of CYP1A1 are positively linked with various malignancies, such as breast, esophageal and smoking-related lung and small intestine cancer [ 22 26 ]. Genotyping and epidemiological studies of CYP1A1 were correlated with increased risk for brain tumor [ 27 29 ]. CYP1B1 is a tumor-associated protein, which has been shown to be overexpressed in various malignant tumors [ 4 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of CYP1A1 are positively linked with various malignancies, such as breast, esophageal and smoking-related lung and small intestine cancer [ 22 26 ]. Genotyping and epidemiological studies of CYP1A1 were correlated with increased risk for brain tumor [ 27 29 ]. CYP1B1 is a tumor-associated protein, which has been shown to be overexpressed in various malignant tumors [ 4 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study represents the largest series of pediatric brain tumor cases assembled for genetic association testing to date. The association between the 29 SNPs investigated in this study and the risk of PBTs has not been examined in previous studies (8)(9)(10)(11). The SNPs were selected a priori for analyses in this study based on findings in GWAS on adult glioma, and our significant findings of associations between SNPs in CDKN2BAS, TERT, RTEL1 and CCDC26, and risk of PBTs were consistent with findings on adult brain tumors with respect to the direction of ORs for the minor alleles (4-7).…”
Section: Discussionmentioning
confidence: 88%
“…Although large genetic studies on adult brain tumors have been conducted (3)(4)(5)(6)(7), very few and only small studies of brain tumors in children and adolescents have been reported (8)(9)(10)(11). In the last few years, four genome-wide association studies (GWAS) on adult glioma identified seven susceptibility loci at 5p15.33 (TERT), 8q24.21 (CCDC26), 9p21.3 (CDKN2A-CDKN2B), 20q13.33 (RTEL1), 11q23.3 (PHLDB1) and 7p11.2 (EGFR) (4-7).…”
Section: Introductionmentioning
confidence: 99%
“…The PubMed database was searched (up to December 2012) using combinations of the following terms: ‘brain tumor’, ‘single nucleotide polymorphism’, ‘association’, ‘gene’, ‘risk’, ‘case control’, ‘susceptibility’, and ‘polymorphism’ to identify all the published peer-reviewed candidate gene-association studies of brain tumors. All the statistically significant SNPs reported by childhood brain tumor genetic association studies [ 11 13 ] as well as the SNPs reported by at least two candidate gene-association studies as being statistically associated with the risk of adult brain tumors [ 3 9 , 44 49 ] were selected for genotyping.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas a considerable number of candidate gene-association studies are available on adult brain tumors, very few and small genetic studies have been performed on brain tumors in children and adolescents [ 10 13 ], due to difficulties in collecting a sufficient number of DNA samples. Hence, the role of genetic polymorphisms in pediatric brain tumor (PBT) etiology is largely unknown.…”
Section: Introductionmentioning
confidence: 99%